The effect of training and educating the community in improving the behavior of dealing with paramedics - Awadh Ahmed Abdullah ALshamrani; Faez Maiuf Saleh Alautbe; Tariq Awadh Mohamed Alshahrani; Naif Helal Muqaybil Alnefaie; Hamad Majdi Al Suwailem; Mohammed Ali Alseghair; Nawaf Mohammed Aldawood (International Journal of Medical Toxicology and Legal Medicine, 2024)
The current study aimed to identify the role of training and education in developing the capabilities of paramedics in providing the services required of them by measuring this role on a set of aspects, the most important of which are personal skills, self-confidence, and the ability to make appropriate decisions at the right time. The study also recommends the need to work on developing and training paramedics periodically and continuously to ensure increasing the effectiveness of paramedics and carrying out their roles in a positive and effective manner by employing the training courses they receive in their field of work.